Student Communication Ethics to Lecturers Through Information and Communication Technology Media - Berkat Persada Lase; Fatiani Lase (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to reveal the communication ethics of Nias University students to lecturers, the causal factors and the efforts made in developing communication ethics for Nias University students to lecturers through information and communication technology media. This research uses qualitative research with descriptive methods. The instrument in qualitative research is the researcher himself. The selection of research subjects was made by purposive sampling technique. Data collection techniques are interviews, observation, and documentation. The data that has been collected is analyzed using the Miles and Huberman analysis model, which includes data reduction, data presentation and conclusion drawing/verification. The study's results revealed that the Communication Ethics of Nias University Students to Lecturers through Information and Communication Technology Media (Mobile Telephone) was still lacking. It is shown from 1). The content of the message (SMS) submitted by students is considered disrespectful; 2). Use of wrong punctuation or usage of abbreviated letters; 3). Students, without further ado, show their needs without thinking about the condition of the lecturer. The factors that cause the low communication ethics of Nias University students to lecturers are the individual nature of students who do not know how to communicate good ethics to lecturers, and the habit of texting to friends is equated to lecturers. Efforts made in developing communication ethics for Nias University students to lecturers are giving warnings and advising students, as well as showing how to communicate with lecturers and conveying the right time to contact lecturers.